2016
DOI: 10.5505/agri.2016.94546
|View full text |Cite
|
Sign up to set email alerts
|

Is Lornoxicam Better Than Low-Dose Tramadol for Post-thyroidectomy Pain?

Abstract: summaryObjectives: the present study sought to compare the analgesic efficacy and adverse effects of intravenous (IV) lornoxicam and tramadol to investigate if lornoxicam is a reasonable alternative to a weak opioid for post-thyroidectomy pain. Methods: Fifty patients of American Society of Anesthesiologists class I or II, 18 to 65 years of age, and who underwent thyroidectomy were assigned to 2 groups in a randomized manner. Group L received 8 mg of lornoxicam IV and Group t received 1 mg/kg of tramadol IV at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
2
6
0
2
Order By: Relevance
“…Consistent with previous studies [3033], 80.0% of patients had NRS scores lower than 4 (only one patient had a NRS score of greater than 6), indicating that thyroidectomy causes mild to moderate postoperative pain. Additional rescue analgesics were not usually required, and the need for additional rescue analgesics did not significantly differ between the groups.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies [3033], 80.0% of patients had NRS scores lower than 4 (only one patient had a NRS score of greater than 6), indicating that thyroidectomy causes mild to moderate postoperative pain. Additional rescue analgesics were not usually required, and the need for additional rescue analgesics did not significantly differ between the groups.…”
Section: Discussionsupporting
confidence: 90%
“…[7] In another study, time until first analgesic demand was 7 hrs for the 16 mg lornoxicam group and 5.5 hrs for the 100 mg tramadol group. [8] Evaluations according to VRS showed that 16 mg lornoxicam values for the first 30 mins were highly significantly lower compared to the 8 mg lornoxicam group and significantly lower than the 100 mg tramadol group. Later evaluations showed that the tramadol group had lower VRS scores compared to the lornoxicam groups.…”
Section: Discussionmentioning
confidence: 90%
“…Yücel et al found that time to first analgesic was significantly longer ( P = .045) and Numeric Rating Scale (NRS) scores at 15 minutes, 30 minutes, and 1 hour were lower in the lornoxicam group ( P = .022). 15 Smirnov et al investigated the use of etoricoxib versus placebo and found that while no there was no difference in amount of rescue and time to first rescue, a significant decrease was seen in number of patients requesting medication ( P = .039). 18 The most common reported side effect was nausea and vomiting (34.5%), followed by bleeding (11.8%) and dizziness (8.3%) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported on the use of nonsteroidal anti-inflammatory drugs (NSAIDs) for perioperative analgesic control in thyroid surgery. [13][14][15][16]18,42 All included studies were prospective RCTs. The summary of data for these studies is listed in Supplemental Table 2 online.…”
Section: Nsaidmentioning
confidence: 99%